[RETRACTED ARTICLE] The Influence of Digital Transformation Capability on Financial Performance of Hotel Businesses in Thailand - Sungthong, Sirinthra (Arts of Management Journal, 2025)
This article has been retracted from the system due to the discovery and complaint that it used inaccurate references and references to the complainant, causing damage and possible misunderstandings, and is also considered unethical research.